The valuation of ecosystem services from the Totonac indigenous worldview - López Santiago, Marco Andrés (Instituto de Ecología, A.C., 2019)
The Totonac culture is characterized by having a richness of knowledge about the use and management of natural resources; nevertheless, due to several factors, there has been a decrease in the conservation and transmission of such knowledge. Hence, the main objective of this work was to describe the different ecosystem services of the flora of a Totonac population, in order to contribute to the preservation of traditional knowledge. The municipality of Filomeno Mata, Veracruz, Mexico was chosen as the case study. This municipality is characteristic of the mountain region of totonacapan. To meet the objective, semi-structured interviews were applied to the target population in 2016. There were talks with key informants and a field trip through a directed transect that served for the observation and collection of the species. It was found that the ecosystem services most recognized by the population are grouped into four categories; in order of importance, the most named were placed in the category of supply, information, habitat and regulation, respectively. It was concluded that there is a need to conduct multidisciplinary studies in indigenous communities for the rescue and preservation of valuable knowledge about the use of natural capital, as well as the understanding of the indissoluble association between culture and ecosystems. Local actions to protect and restore ecosystems, benefit both direct and indirect users at the national or international scale.